PENGARUH KOMPETENSI KARYAWAN DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN BANK DANAMON CABANG TUANKU TAMBUSAI PEKANBARU - Boy Aulia Sastra; Zulfadil '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Bank Danamon Indonesia Tbk Branch Pekanbaru. The purpose of this study was to determine the effect of employee competencies and workload simultaneously and partly on employee performance. The population of this study were employeestotaling 89 people. Research variables used are the competence of employees and workload as independent variables and employee performance as the dependent variable. Data analysis method used is multiple linear regression analysis.Calculation of partial, competence of employees affect the performance of employees. Furthermore, the workload impact on employee performance. Simultaneously, employee competence, workload and performance of employees affect the performance of employees.Keywords:Competence of Employees, Workload and Employee Performance